Analysis of Offline and Online Learning Processes During the Covid-19 Pandemic - Fatimah, Fatimah; Susiati, Susiati; Suherman, La Ode Achmad; Tinggapy, Hasanudin; Goa, Ivana; Yulismayanti, Yulismayanti (SAINTIS Publishing, 2023)
The purpose of this study is to assess the offline and online learning process at Namlea State Primary School 5 (SDN 5 Namlea) during the Covid-19 pandemic and to identify the teacher's approach for integrating offline and online learning during the Covid-19 pandemic at SDN 5 Namlea. This study employed a qualitative descriptive methodology with a phenomenological approach. Principals, instructors, students in Classes I, III, IV, and VI, and students in Classes III, IV, and V served as data sources for both primary and secondary data. This research employs nonparticipant observation employing field survey techniques (field study), interviews (interviews), documentary studies, and literature studies as its methodology. During the Covid-19 epidemic, the results of the study demonstrate that the offline and online learning processes at SDN 5 Namlea are very efficient and effective. The school incorporates offline learning through 1) shift (alternating teaching and learning), 2) television, 3) study groups, and 4) home visits. In the process of online education, teachers utilize two media platforms, namely WhatsApp and YouTube. During the Covid-19 pandemic, SDN 5 Namlea implemented offline and online learning strategies by 1) conducting learning activities (Blended Learning, Offline, Online); 2) using technological facilities such as gadgets, laptops, internet, and wifi; and 3) utilizing application media, namely WhatsApp and YouTube.